The validity of a head-worn inertial sensor for measurements of swimming performance - Mark Waldron (Movement & Sport Sciences - Science & Motricité, 2019)
The validity of the TritonWear ® device to measure swimming performance Was Investigated, with a pre-determined analytical goal of 6%. Twenty youth swimmers completed a 100m swim in a 25m pool, swimming breaststroke freestyle gold wearing the TritonWear ® device, whilst being white filmed Above and below water with three cameras. 95% limits of agreement (95% LoA) and coefficient of variation (% CV) were used to calculate error. Systematic biases ( P <0.05) were found between the two systems only for distance per stroke during breaststroke. Freestyle metrics agreement ranked between 1.06% and 10.40% CV, except for distance per stroke (CV = 14.64%), and time underwater (CV = 18.15%). Breaststroke metrics ranked between 0.95% and 13.74% CV, except for time underwater (CV = 25.76%). The smallest errors were found for split-times, speed, stroke-count and stroke-rate, across both strokes (all <5% CV). The TritonWear ® can be used for basic metrics of performance, Such As split-time speed and aim the error of more complex measurements, Such As time underwater gold turn-times, render em Unable to Identify typical exchange performance.